THU0017 IN VITRO MECHANISTIC STUDIES DEMONSTRATE FILGOTINIB ACTIVITY THAT HAS POTENTIAL IMPLICATIONS FOR DIFFERENTIATION AMONG JAK INHIBITORS. (June 2019) - Han, Pei; Meng, Amy; Mollova, Nevena; Yu, Yuanjiang; DI Paolo, Julie A.
Abstract : Background: Inhibition of the Janus kinase-signal transducers and activators of transcription (JAK-STAT) pathway has demonstrated efficacy in immune-mediated diseases and has been identified as a therapeutic target for the treatment of rheumatoid arthritis (RA). Differences in JAK inhibitor specificity for JAK1, JAK2, JAK3, and TYK2 may influence their safety profiles, but the mechanism is not known. Selective JAK1 inhibition by filgotinib (FIL) may modulate a subset of proinflammatory cytokines associated with RA pathogenesis and improve the risk-benefit profile by minimizing other non–JAK1-related adverse events. JAK2 inhibition is associated with cytopenias, while JAK3 inhibition has been associated with increased risk for opportunistic infections (eg, tuberculosis and herpes zoster) and chronic low-grade inflammation. In clinical trials, FIL did not negatively impact hemoglobin, LDL/HDL ratios, or natural killer (NK) cell counts. 1-3 Objectives: To compare the in vitro profile of JAK inhibitors with different JAK selectivity profiles, for effects on erythroid progenitor cell expansion, NK cell proliferation, and liver X receptor (LXR) agonist-induced cholesteryl ester transfer protein (CETP) expression, an enzyme responsible for the conversion of HDL to LDL. Methods: JAK inhibitors (FIL, FIL metabolite [GS-829845], baricitinib [BARI], tofacitinib [TOFA], and upadacitinib [UPA]) were evaluated in vitro in human cell-based assays: growth of erythroid progenitors from human cord blood CD34 + cells using a HemaTox™ liquid expansion assay, IL-15–induced NK cell proliferation, and LXR agonist-induced CETP expression in the hepatic cell line (HepG2). Using IC50 s generated from these assays and the reported human plasma concentrations of the JAK inhibitors from clinical studies, 4-6 we calculated the target coverage for each compound at clinically relevant doses. The activity of FIL in humans was based on a PK-PD modeling algorithm 7 of FIL + GS-829845. Results: In vitro assay results are described in the table. Based on these results, human exposure data, and modeled PK-PD relationships, FIL 100 mg and FIL 200 mg result in lower calculated cellular inhibition than the other JAK inhibitors at clinical exposures. Notably, FIL 100 mg and FIL 200 mg, but not the other inhibitors, are calculated to reduce CETP expression by 17% and 27%, respectively, while BARI, TOFA, and UPA are not expected to alter CETP levels. a Weak stimulation of LXR agonist-induced CETP expression. Conclusion: JAK1 selectivity of FIL and GS-829845 resulted in less inhibition of erythroid progenitor expansion and NK cell proliferation compared with BARI, TOFA, and UPA. FIL also reduced LXR agonist-induced CETP expression, while the other inhibitors did not alter these levels. These results provide a potential mechanistic link to the observed reduction of CETP concentration and activity following FIL treatment, and the observed reduction in LDL:HDL in RA patients. 8    References: [1] Kavanaugh A, et al. Ann Rheum Dis. 2017;76:1009-1019. [2] Westhovens R, et al. Ann Rheum Dis. 2017;76:998-1008. [3] MC Genovese, et al. ACR 2018. Abstract L06. [4] Shi JG. J Clin Pharmacol. 2014;54:1354-1361. [5] Lamba M. J Clin Pharmacol. 2016;56:1362-1371. [6] Mohamed MF, et al. Clin Pharmacokinet. 2016;55:1547-1558. [7] Tuk B. J Pharmacol Exp Ther. 1999;289:1067-1074. [8] Galien R. Arthritis Rheumatol. 2015;67(suppl 10). Disclosure of Interests: Pei Han Shareholder of: Gilead Sciences, Inc., Grant/research support from: Gilead Sciences, Inc., Employee of: Gilead Sciences, Inc., Amy Meng Shareholder of: Gilead Sciences, Inc., Employee of: Gilead Sciences, Inc., Nevena Mollova Shareholder of: Gilead Sciences, Inc., Employee of: Gilead Sciences, Inc., Yuanjiang Yu Grant/research support from: Gilead Sciences, Inc., Employee of: Gilead Sciences, Inc., Julie A. Di Paolo Shareholder of: Gilead Sciences, Inc., Employee of: Gilead Sciences, Inc.